Thermo-Optic Switch with High Tuning Efficiency Based on Nanobeam Cavity and Hydrogen-Doped Indium Oxide Microheater - Weiyu Tong; Shangjing Li; Jiahui Zhang; Jianji Dong; Bin Hu; Xinliang Zhang (Photonics, 2024)
We propose and experimentally demonstrate an efficient on-chip thermo-optic (TO) switch based on a photonic crystal nanobeam cavity (PCNC) and a hydrogen-doped indium oxide (IHO) microheater. The small mode volume of the PCNC and the close-range heating through the transparent conductive oxide IHO greatly enhance the coupling between the thermal field and the optical field, increasing the TO tuning efficiency. The experimental results show that the TO tuning efficiency can reach 1.326 nm/mW. And the rise time and fall time are measured to be 3.90 and 2.65 μs, respectively. In addition, compared with the conventional metal microheater, the measured extinction ratios of the switches are close (25.8 dB and 27.6 dB, respectively), indicating that the IHO microheater does not introduce obvious insertion loss. Our demonstration showcases the immense potential of this TO switch as a unit device for on-chip large-scale integrated arrays.